(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
In this experimental work. the effective cross section was measured for the interaction of gamma ray photons from different radioactive sources with absorbent materials by the linear attenuation coefficient. Where Lead. iron and aluminum were used as absorbents in this work. And the sources of radiation are and the mixed source, which gives the spectral lines corresponding to the The absorbent material between the radioactive source and the detector was placed. The absorbent material thickness was increased from 0.5cm to 5cm by 0.5cm per measurement to calculate the number of particles that traversed the thickness of the absorbent material during 300s time. The linear attenuation coefficient can be calculated By representing the logarithm of the number of particles recorded by the detector N(X) as a function to the thickness of the absorbent material x then The effective cross section of the absorbent material was calculated from the relationship between them: Where n is the number of atoms from the absorbent material in the volume unit. and this number has been calculated for the three substances .